Migraine headache prevalence in Taif city, Saudi Arabia - Hassan, Khaled M.; Addas, Omar K.; Alharthy, Fatma T.; Banan, Ahmed A.; Alhazmi, Asalah A.; Dabi, Montaha M.; Al-Ansari, Ghada A.; Albouq, Abdulrahman F.; Alhowety, Afrah S.; Alhamad, Abdulrahman I.; Aleissa, Abdulaziz I.; Alshebly, Ahmad T.; et al. (International Journal Of Community Medicine And Public Health, 2020)
Background: Migraine is a public health concern and is the third most common cause of disability for individuals below the age of 50. Despite the multiplicity of studies on the epidemiology and nature of diseases around the world, except from Saudi Arabia. Present study was conducted to see the prevalence of migraine in Taif city, Saudi Arabia. Methods: This was a cross sectional analysis of 354 individuals in Taif area. Data were collected via a self directed questionnaire, including demographic variables, clinical variables and therapeutic variables. Data was moved to the device and analyzed using SPSS software. Results: As a result, of the 354 recruited participants, 54% were female and 46% were male. Migraine existed in 89.9% of the urban population. About 24% of migrants were unemployed, and 16% were non workers. Headache found in 71.6% of males and 86.9% of females (p=0.002). Gender has been substantially associated with migraine prevalence (odds ratio 0.28). Approximately 47% posted a pain score of 4-6. In 32.4% of females and 26.6% of males, medical advice was sought. Nausea occurred in more than one-third of patients before and after a headache. Just 31.4% of participants were conscious of migraine causes. Conclusions: The past of the family was found in 64% of the participants. In Taif city, migraine is prevalent. It is more prevalent among women and urban areas.